Liquid–solid equilibria and supercooling of Custodiol® in isochoric thermodynamic systems at subfreezing temperatures - Ștefan Ioan Câmpean; George Andrei Beșchea; Maria Bianca Tăbăcaru; Alexandru Șerban; Irinel Popescu; Florin Botea; Boris Rubinsky; Gabriel Năstase (AIP Publishing, 2023)
There is growing interest in using isochoric freezing and isochoric supercooling for the preservation of biological matter at subfreezing temperatures. CustodiolVR is a commonly used intracellular composition type, subnormothermic preservation solution. It is anticipated that CustodiolVR will also be used for isochoric freezing and isochoric supercooling preservation of biological matter. The thermodynamic properties of CustodiolVR at subfreezing temperatures as well as the metastable behavior of the solution at subfreezing temperatures were not studied in the past. This study was designed to generate the thermodynamic data needed for the use of CustodiolVR for the preservation of biological matter in isochoric systems at subfreezing temperatures. The experiments were performed in a specially designed isochoric chamber that can measure simultaneously the temperature and pressure in the isochoric chamber, and thereby correlate pressure and temperature at thermodynamic equilibrium in isochoric systems as well as the nucleation temperature in isochoric supercooling. The primary focus of this study is on determining the temperature at which nucleation is initiated and to identify the temperature threshold for nucleation due to its specific relevance to various applications in medicine.